Rapid automated W‐phase slip inversion for the Illapel great earthquake (2015, Mw = 8.3). Issue 5 (5th March 2016) - Benavente, Roberto; Cummins, Phil R.; Dettmer, Jan
Abstract: We perform rapid W‐phase finite fault inversion for the 2015 Illapel great earthquake ( M w = 8.3). To evaluate the performance of the inversion in a near real time context, we divide seismic stations into four groups. The groups consider stations up to epicentral distances of 30°, 50°, 75°, and 90°, respectively. The results for the first group could have been available within 25 min after the origin time and the results for the last group within 1 h. The four results consistently show a peak slip of ∼10 m near the trench with trench perpendicular rake which is consistent with the tsunami genesis of the event. The slip location is similar to that in the preliminary U.S. Geological Survey solution. The inversion is automated and provides meaningful results within 25 min after the event. This makes the method particularly suited to emergency management and early warning at regional and teletsunami distances. Key Points: An approach for automated, rapid finite slip inversion for megathrust earthquakes is developed The objective and robust inversion relies only on waveforms of the early arriving W‐phase A solution for the 2015 Illapel event could heave been obtained within 25 min from origin time